Development of Video Tutorial Learning Media for Fashion Illustration Using Photoshop - Oktriana, Vern Edlyn; Yusmerita, Yusmerita (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Due to a dearth of video tutorials, only a small percentage of students are proficient in digital design creation, especially for creating digital designs using digital applications. Students find it difficult to operate the Photoshop application and are unfamiliar with the functions of its tools. This study aimed to evaluate the reliability of video lesson materials for fashion illustration design using the Photoshop application for the 2022 fashion students at Universitas Negeri Padang. The Research and Development (R&D) approach, using the 4D model, was the methodology used in this research. Primary data was collected using questionnaires, interviews, and observations. A scoring sheet with an explanation of the Likert scale was used as the study instrument. Data analysis was the method utilized in this research the media validity test findings yielded a 94.56% score, and the material expert validity obtained a score of 89.08%, resulting in a total score of 91.82%, which falls into the 'very valid' category. Meanwhile, a score of 92.22% was earned in the practicality administered by the course lecture. The small group practicality trial had a score of 96.4%, and the large group trial scored 85.45%, both indicating a 'very practical' category. In conclusion, the video tutorial media can be used as a learning media in the Fashion Illustration lecture process.